Panax notoginseng Saponins for Treating Coronary Artery Disease: A Functional and Mechanistic Overview - Duan, Lian; Xiong, Xingjiang; Hu, Junyuan; Liu, Yongmei; Li, Jun; Wang, Jie (Frontiers in Pharmacology, 2017)
Coronary artery disease (CAD) is a major public health problem and the chief cause of morbidity and mortality worldwide. Panax notoginseng, a valuable herb in traditional Chinese medicine (TCM) with obvious efficacy and favorable safety, shows a great promise as a novel option for CAD and is increasingly recognized clinically. Firstly, this review introduced recent clinical trials on treatment with PNS either alone or in combination with conventional drugs as novel treatment strategies. Then we discussed the mechanisms of P. notoginseng and Panax notoginseng saponins (PNS), which can regulate signaling pathways associated with inflammation, lipid metabolism, the coagulation system, apoptosis, angiogenesis, atherosclerosis, and myocardial ischaemia.